Fungsi Taman Kota Untuk Mitigasi Dampak Urban Heat Island di Kota Bandung: Ecological Function of Forest Park to Mitigate Urban Heat Island in Bandung - Rosleine, Dian; Irfani, Arka (Jurnal Sumberdaya Hayati, 2020)
Forest parks can take a role in mitigating negative impact of Urban Heat Island. Therefore, this study was conducted to clarify ecological function of three forest parks i.e Ganesha, Maluku, and Tegalega forest park in mitigating Urban Heat Island. Land classification and surface temperature were determined by analyzing Landsat 8 image with QGIS. Air temperature was measured by mobile station through north-south and east-west of Bandung City area. There are four types of land classification in Bandung as follows: settlements, water body, bare soil, and vegetation. In Bandung City, vegetation cover is around 20.72%; surface temperatures in the afternoon varies from 23 to 39.6°C, while during the night air temperatures varies from 20.5 to 24.9°C. Northern part of Bandung tends to have cooler air temperature due to high coverage of vegetation. Tegalega forest park can reduce temperature up to 2.6°C, while in Maluku forest park is 1.98°C and Ganesha forest park is 0.75°C. Therefore, the existence of forest parks is important in urban area because they can take a part to reduce negative impact of Urban Heat Island.